Increased group II phospholipase A2 in colonic mucosa of patients with Crohn's disease and ulcerative colitis. Issue 11 (November 1994) - Minami, T; Tojo, H; Shinomura, Y; Matsuzawa, Y; Okamoto, M
Abstract : The immunochemical protein content of group II phospholipase A2 (PLA2) and PLA2 enzymatic activity were measured for colonic mucosal biopsy samples obtained from patients with either Crohn's disease of the colon or ulcerative colitis, and control patients without inflammatory bowel disease. Immunoreactive group II PLA2 (IR-PLA2 II) content and PLA2 activity in actively inflamed colonic mucosa of Crohn's disease patients were significantly higher than those in inactively inflamed mucosa of Crohn's disease patients and the colonic mucosa of controls. IR-PLA2 II content and PLA2 activity in severely inflamed mucosa of ulcerative colitis patients were significantly higher than those in the colonic mucosa of the controls. Mucosal PLA2 enzymatic activity was closely correlated with mucosal IR-PLA2 II content in patients with Crohn's disease and ulcerative colitis. These results suggest that an increase in PLA2 enzymatic activity in inflamed colonic mucosa of Crohn's disease and ulcerative colitis was mainly attributed to increased protein content of group II PLA2, and that an increase in mucosal group II PLA2 may be involved in the pathogenesis of intestinal inflammation of Crohn's disease and ulcerative colitis.